Influence of Organization Culture, Leadership, Motivation, Discipline And Compensation Toward Public Health Center Performance - Sa'adah, Noor; Rahmawati, Salis Diah; Astuti, Jannah Puji; Suprapti, Suprapti; Astuti, Rulyta Yuli; Sudargini, Yuli (Journal of Industrial Engineering & Management Research, 2020)
The aim of this study is to analyze the effect of organization culture, leadership, motivation, compensation and discipline toward Public Health Center Performance. The method used in this study is quantitative method. Data was collected by distributing questionnaires to 90 staff of public health center in Pati Central Java . For questions about the identity of respondents designed in the form of a semi-open questionnaire in addition to a closed questionnaire. Data collection technique is using questionnaire with Likert Scale. Analysis from this study is SEM (Structural Equation Model) with SmartPLS version 3.0 as a statistic tools. Based on the results of data analysis through a questionnaire distributed to respondents, found several conclusions , There is a significant effect of organization culture on public health center Performance. There is a significant effect of leadership on public health center Performance and There is a significant effect of motivation on public health center Performance. There is a significant effect of compensation on public health center Performance. There is a significant effect of discipline on public health center Performance.